Implications of shunt morphology for the surgical management of extrahepatic portosystemic shunts - White, R.N.; Parry, A.T.; Shales, Chris (Wiley, 2018)
Objectives: To describe the implications of extrahepatic portosystemic shunt morphology for 14 the chosen site of shunt closure in dogs and cats. Methods: A retrospective review of a consecutive series of dogs and cats managed for 16 congenital extrahepatic portosystemic shunts was used. Results: In total 54 dogs and 10 cats met the inclusion criteria revealing five distinct shunt 18 types; left gastro-phrenic, right gastro-caval (types Ai, Aii and Aiii), spleno-caval, colo-caval 19 and left gastro-azygos. Without exception, findings of computed tomography angiography and 20 direct gross observations at the time of surgery confirmed four consistent sites of 21 communication between the anomalous shunting vessel and the systemic venous system; the 22 caudal vena cava at the level of the epiploic foramen, the left phrenic vein at the level of the 23 oesophageal hiatus, the azygos vein at the level of the aortic hiatus and the caudal vena cava 24 or iliac vein at the level of the sixth or seventh lumbar vertebrae. The use of intra-operative mesenteric portography was effective in confirming that at the time of surgery all portal 26 tributary vessels were proximal to the point of shunt attenuation. Conclusions: Findings confirmed that for the common types of extrahepatic portosystemic 28 shunts seen there were only four consistent sites of communication between the shunt and the 29 systemic venous system. This information supports the use of a systematic approach for 30 location and attenuation of shunts in dogs and cats.